2020
DOI: 10.2147/dmso.s253632
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bone Morphogenetic Protein-2 and Osteopontin Gene Expression in Epicardial Adipose Tissue from Patients with Coronary Artery Disease Is Associated with the Presence of Calcified Atherosclerotic Plaques</p>

Abstract: It has been proposed that the cardiovascular effects of obesity are related to epicardial adipose tissue (EAT), which seems to play an active role on the development and calcification of atherosclerotic plaques, but the mechanisms are still unknown. Therefore, the aim of this study was to determine whether the EAT expresses the genes of calcifying factors and whether such expression is associated with the body mass index (BMI) and with the presence of coronary artery calcium (CAC) in patients with coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
7
0
1
Order By: Relevance
“…In humans, OPN expression increases in the epicardial fat of patients with CAD compared to control subjects and is associated with the presence of calcified atherosclerotic plaques. [145] We have confirmed that senescent CD153 + PD-1 + CD44 hi CD 4+ T cells markedly increased and produced a large amount of OPN in the epicardial fat of HFD-induced obese mice (K. Shirakawa, unpublished observation). These findings suggest that senescent CD 4+ T cells in epicardial fat, at least in part, contribute to the development and worsening of CVD in obese patients.…”
Section: Plasma Opn Levels Predict Prognosis In Patients With Cardiovascular Diseasessupporting
confidence: 68%
See 1 more Smart Citation
“…In humans, OPN expression increases in the epicardial fat of patients with CAD compared to control subjects and is associated with the presence of calcified atherosclerotic plaques. [145] We have confirmed that senescent CD153 + PD-1 + CD44 hi CD 4+ T cells markedly increased and produced a large amount of OPN in the epicardial fat of HFD-induced obese mice (K. Shirakawa, unpublished observation). These findings suggest that senescent CD 4+ T cells in epicardial fat, at least in part, contribute to the development and worsening of CVD in obese patients.…”
Section: Plasma Opn Levels Predict Prognosis In Patients With Cardiovascular Diseasessupporting
confidence: 68%
“…Epicardial and pericardial fat are associated with cardiovascular risk [ 142 , 143 , 144 , 145 ]. In humans, OPN expression increases in the epicardial fat of patients with CAD compared to control subjects and is associated with the presence of calcified atherosclerotic plaques.…”
Section: Immunosenescence In Cardiovascular Diseasesmentioning
confidence: 99%
“…It should be noted that PCL/PLGA-PEI scaffolds with sustaining BMP2 release had the best promoting effect on the in vitro differentiation of stem cells. Continuous BMP2 supply, whether free or from polyester loading, can upregulate the expression levels of molecular markers related to the bone differentiation, such as Runx2 [ 54 , 55 ], OPN [ 56 , 57 ], COL-1 [ 58 ] and OCN [ 59 ], as well as simultaneously downregulate the expression of BSP [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fetuin-A itself may inhibit VSMC-related calcification via inhibition of apoptosis of VSMCs, promotion of clearance of apoptotic bodies released by VSMCs, and inhibition of intracellular mineralization of matrix vesicles of VSMCs [149][150][151][152][153][154][155] .…”
Section: Discussionmentioning
confidence: 99%